In the name of the Other? Refugee theatre and the value of "illegal" life in Britain. Issue 1 (2nd January 2016) - Helff, Sissy
Abstract: Drawing on refugee theatre performances by companies such as ice&fire, this article explores the politics of Testimonial Refugee Theatre in Britain and how illegal life is performed in contemporary verbatim theatre productions. Within the realm of narratives of flight, political drama holds an important position as a genre, because of its ability to create intimate immediacy. In theatre halls and post-performance gatherings, audiences can feel ready to inquire about politics. The variety of theatre productions dealing with refugee issues is enormous and refugee theatre adds new dimensions to discussions concerning Britain as a post-racial society. Contemporary refugee theatre in general, and its two major subgenres Container Plays and Testimonial Refugee Plays in particular, function as dramatic buffer zones which signal post-racial dimensions while re-inscribing alienation into the cultural and social make-up of British society. The plays discussed include Kay Adshead's The Bogus Woman, Sonja Linden's I Have Before Me a Remarkable Document Given to Me by a Young Lady from Rwanda, Clare Bayley's The Container and Sylvie Hoffmann and Aimé Kongolo's White Goods . Influential international productions such as Théâtre du Soleil's Le Dernier Caravanserail (Odyssées) directed by Ariane Mnouchkine and Christoph Schlingensief's container performance spectacle Big Brother, Foreigners Out! ( Ausländer Raus! 2000) serve as background screens against which the arguments unfold.